Pengaruh Kualitas Produk Dan Promosi Terhadap Minat Beli - Nady Rizky Ardiansyah; Budhi Wahyu Fitriadi; Rita Tri Yusnita (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
This study aims to determine the effect of product quality and promotion simultaneously on purchase intention at Sibungsu Singaparna Donuts, Tasikmalaya Regency. The effect of product quality and promotion partially on buying interest in Donat Sibungsu Singaparna, Tasikmalaya Regency. The method used in this research is quantitative with a survey approach. With a research sample of 100 people as respondents Donat Sibungsu Singaparna Tasikmalaya. The data used is primary data. The analytical tool used in this study is multiple linear regression using the SPSS support application version 25. Simultaneously product quality and promotion have a significant effect on purchase intention Partially, the product quality variable has a significant effect on purchase intention, as well as the promotion variable, which partially has a significant effect on purchase intention.